Post-harvest handling of cormels, leaves and inflorescence of cocoyam in terms of processing in Kogi East Agricultural Zone of Kogi State, Nigeria - Alexander, Ojonugwa; Mohd Sufian Kang, Enio Kang (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
This paper is aimed at investigating the post-harvest handling of cormels leaves, and inflorescence of cocoyam in terms of processing in Kogi East Agricultural Zone of Kogi State, Nigeria. A sample of 27 Cocoyam farm families were purposively selected from the nine Local Government Areas in the zone. The data were collected using Focus Group Discussion (FGD), tape recorded and interpreted. The results indicated that farmers of cocoyam can traditionally process cocoyam cormels into flour, formulate livestock feeds using cocoyam flour, and process cocoyam leaves, petiole, and inflorescence into food condiments aimed at enhancing preservation and storage for future usage. The study concluded that cocoyams are high in coagulating contents, contain little protein and lipid, has significant potential for livestock feed, provide materials for renewable energy source, and industrial raw materials which place them as major food and cash crops. The study therefore recommended, amongst others, that hard work should be put in place by Extension Agents to educate cocoyam farmers on the high dietary worth of cocoyam hence the need for the farmers’ involvement in various forms of its processing.